Ciberarte: uma aproximação em 3 dimensões [semióticas] - Garcia, Vívian Mara Silva (2006)
This study is based on the assumption that art is a powerful form of expression which carries the strength of mutations, producing original perceptions that renew societies. To investigate the state-of-art of art, its trends, characteristics, manifestations or tools, I opted to searching cyberart – a new and complex form of artistic expression that has cyberculture as its native context, and the union of art and science as its base. Therefore, to understand this new practice, the cyberart phenomenon was approached, starting with a short review of the artistic processes of the past and its transformations towards digital art. After that, I described the new supports – hypermedia and cyberspace – as well as the new tools, because ink, brushes or any other instruments usually used by artists for the accomplishment of their artwork are no longer used in cyberart. Finally, a ‘script’ based on Charles S. Peirce’s theory of signs was used to analyze three different pieces of cyberart, according to the purpose of this study.